Persepsi Followers Terhadap Personal Branding Digital : Studi Kasus Akun Tiktok @Khairainsyira - Vhiona Rizkia Fadilah (Jaanur Elbarik Indonesia, 2026)
This study aims to understand and analyze followers’ perceptions of the digital personal branding built by the Tiktok account @Khairainsyira_. This study uses a qualitative approach with a descriptive method. Data was obtained through semi-structured in-depth interviews with seven followers selected using purposive sampling techniques, supported by observations of uploaded content. The results show that the digital personal branding of @Khairainsyira_ is perceived positively by followers. Khaira is seen as a friendly, calm, honest, and consistent figure in presenting her self-image. Consistent content, authenticity of personal branding, natural communication style, and active interaction with followers are the main factors in building audience trust. Additionally, the content shared has a positive impact in the form of inspiration for fashion style, increased self-confidence, and motivation for followers. Thus, this study concludes that strong digital personal branding is not only determined by content quality, but also by the value of attitude, communication ethics, and emotional closeness between creators and audiences on social media.